Decarbonising steel production using CO2 Capture and Storage (CCS): Results of focus group discussions in a Welsh steel-making community. (January 2021) - Williams, Rhys; Jack, Corin; Gamboa, Davide; Shackley, Simon
Highlights: CCS seen to be able to improve the image of Port Talbot and bring inward investment. Focus group participants seek genuine, open engagement between stakeholders (industry and government) to help build trust. A collective distrust for Port Talbot steel firm and Government to implement CCS. Scientific/research bodies' perceived as most trusted amongst three CCS stakeholders. Main negative view of CCS was that it may pose a threat to industry competitiveness. Abstract: Carbon dioxide Capture and Storage (CCS) is considered a key strategy for decarbonising industries which have limited options for tackling CO2 process emissions. Previous efforts to develop CCS projects have been thwarted by adverse public perceptions amongst other issues. Understanding and tracking public perceptions prior to project development is therefore highly advisable. This study explores public perceptions of applying CCS technology at the Port Talbot Steelworks in South Wales. Opinions of local residents were gathered by means of two focus groups. Participants were concerned about the impact of implementing CCS on the competitiveness of the plant and, as a consequence, the possibility of closure. Perceived positive impacts were that a CCS facility would improve local air quality as well as the town's public image, bringing inward investment. Acceptance or otherwise of CCS was found to be influenced by trust. Participants expressed particular distrust towards the local steel firm and various levels of Government, citing poor engagement, whilst showing tentative trust towards scientific/research organisations. Most participants saw emission reducing technologies as an inevitability, with most considering CCS to be of benefit to the Port Talbot Steelworks. If an effective engagement strategy and equal-voice procedures are applied, the residents of Port Talbot could be amenable to CCS.